PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Irvan, Irvan; Wardan, Khusnul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The quality of education in Indonesia still faces serious challenges, as indicated by the low PISA 2023 scores, despite principals playing a central role in orchestrating the transformation of educational institutions. This research focuses on an in-depth analysis of principals' leadership strategies in improving educational standards through a managerial approach, academic supervision, and technology integration. Using a descriptive qualitative method based on a literature review of scientific documents and journals from the past decade, this study examines effective leadership patterns in addressing the dynamics of the times. The study stages include identifying the implementation of school-based management, analyzing teacher professional development programs, and evaluating the use of digital technology in learning. Key findings indicate that visionary and collaborative transformational leadership has a significant impact on increasing teacher motivation, community participation, and student learning outcomes. Furthermore, ongoing academic supervision has proven to be a vital instrument in maintaining pedagogical quality. The study's conclusions emphasize that principals must act as adaptive agents of change capable of synergizing all school resources, making strengthening managerial and leadership capacity an absolute prerequisite for realizing a superior and globally competitive educational ecosystem. ABSTRAKKualitas pendidikan di Indonesia masih menghadapi tantangan serius yang terindikasi dari rendahnya capaian skor PISA 2023, padahal kepala sekolah memegang peran sentral dalam mengorkestrasi transformasi mutu lembaga pendidikan. Penelitian ini berfokus pada analisis mendalam mengenai strategi kepemimpinan kepala sekolah dalam meningkatkan standar pendidikan melalui pendekatan manajerial, supervisi akademik, dan integrasi teknologi. Menggunakan metode kualitatif deskriptif berbasis studi literatur terhadap dokumen dan jurnal ilmiah satu dekade terakhir, penelitian ini menelaah pola kepemimpinan yang efektif dalam menghadapi dinamika zaman. Tahapan kajian meliputi identifikasi implementasi manajemen berbasis sekolah, analisis program pengembangan profesional guru, serta evaluasi pemanfaatan teknologi digital dalam pembelajaran. Temuan utama menunjukkan bahwa kepemimpinan transformasional yang visioner dan kolaboratif memberikan dampak signifikan terhadap peningkatan motivasi guru, partisipasi masyarakat, dan hasil belajar siswa. Selain itu, supervisi akademik yang berkelanjutan terbukti menjadi instrumen vital dalam menjaga kualitas pedagogik. Simpulan penelitian menegaskan bahwa kepala sekolah harus bertindak sebagai agen perubahan adaptif yang mampu menyinergikan seluruh sumber daya sekolah, sehingga penguatan kapasitas manajerial dan kepemimpinan menjadi prasyarat mutlak demi terwujudnya ekosistem pendidikan yang unggul dan berdaya saing global.